Kinerja KPUD Kota Batu dalam meningkatkan Electoral Activity pada PILGUB Tahun 2018 - Khusnul Khotimah (Departemen Ilmu Pemerintahan Fisip Unhas, 2020)
This study tries to explain the steps or efforts undertaken by the Batu City Election Commission in increasing the political participation of the people of Batu City who have held the election of the Governor and Deputy Governor in 2018. Batu City has a high level of community participation in the regional head election especially PILGUB, the low level of participation in Kota Batu is the reason why the party for democracy is hampered.